DEVELOPMENT OF MATHEMATICS LEARNING DEVICES WITH PROBLEM BASED LEARNING (PBL) MODEL ON STATISTICS MATERIALS FOR SMP/MTs CLASS VIII - Desti Sobriani; Titi Solfitri (Jurnal Prinsip Pendidikan Matematika, 2022)
This study aims to produce mathematics learning tools in the form of a syllabus, lesson plans (RPP), and student worksheets (LKPD) based on a problem-based learning model on statistical material for class VIII junior high school students. This study uses a 4-D development model, which includes four stages, namely: (1) define; (2) design; (3) develop; and (4) dIsseminate. The research instrument used is the instrument of validity and practicality. The validity instrument is in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans, and LKPD. The practical instrument is in the form of a student response questionnaire to the use of LKPD. The learning tools that have been compiled are then validated by three validators and revised according to suggestions from the validators. The valid learning tools were then tested in small groups with the subject of 6 students of class VIII SMP. Based on the results of data analysis and discussion, mathematics learning tools in the form of syllabus, lesson plans and LKPD with a problem-based learning model on statistical material are considered very valid and very practical to be used by junior high school students of class VIII.